margi 2015: International conference on multidisciplinary academic research & global innovation august Beijing China 2015 (global illuminators, 2015)
Population Growth and Economic Oscillations in a Small-Open Growth Model (Wei-Bin Zhang),The Impact of Exchange Rate Movements on Industries Trade Between Indonesia and China (Alhayky, Ahmed, Alhayki, Zainab) How far is Mumbai from New York?: Efficiency of Dually-Listed Indian Stocks (Partha Ray,Vinodh Madhavan) The Implementation of Peer-to-Peer Bandwidth Estimation Mechanism in Multimedia Streaming Networks (Cai, Dong-Liang, Wang, Po-HsuaN Wang, Yung-Chung, Tsai, FuHsiang, Wang, Jenn-Shing) Real-Time Transmiting, on-Line Learning System in Education Field (Cai, Dong-Liang,TsaiMeng-Feng,Wang, Yung-Chung, WangJenn-Shing)